1997
DOI: 10.1038/bjc.1997.358
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive production of multiple cytokines and a human chorionic gonadotrophin beta-subunit by a human bladder cancer cell line (KU-19-19): possible demonstration of totipotential differentiation

Abstract: Summary Bladder cancer cells have been shown to secrete a variety of factors that are not related to cells of urothelial origin. The histogenesis of these tumour developments is uncertain, and a variety of theories have been previously reported. In the present manuscript, we identify the factors constitutively produced by a human bladder cancer cell line ) that was found to produce beta human chorionic gonadotrophin (,B-hCG), granulocyte colony-stimulating factor (G-CSF), granulocyte-macrophage colony-stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 41 publications
(25 reference statements)
0
34
0
Order By: Relevance
“…It can induce migration in some tumour cells (Wang et al, 1990) and has been implicated in the induction of angiogenesis in such diverse diseases as psoriasis (Schroeder and Christopher, 1986), rheumatoid arthritis (de Marco et al, 1991), idiopathic pulmonary fibrosis (Keane et al, 1997) and some malignant diseases (Folkman, 1986(Folkman, , 1990. Previous studies have demonstrated that IL-8 is expressed by lung (Strieter et al, 1995), bladder (Tachibana et al, 1997), prostate (Green et al, 1997) and head and neck squamous carcinomas (Richards et al, 1997), astrocytoma (Van Meir et al, 1992 and malignant melanoma (Schandendorf et al, 1993;Singh et al, 1994). It has been reported that IL-8 acts as an angiogenic factor in lung carcinoma Strieter et al, 1995;Arenberg et al, 1996); however, the function of IL-8 in the other carcinomas has not been clarified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can induce migration in some tumour cells (Wang et al, 1990) and has been implicated in the induction of angiogenesis in such diverse diseases as psoriasis (Schroeder and Christopher, 1986), rheumatoid arthritis (de Marco et al, 1991), idiopathic pulmonary fibrosis (Keane et al, 1997) and some malignant diseases (Folkman, 1986(Folkman, , 1990. Previous studies have demonstrated that IL-8 is expressed by lung (Strieter et al, 1995), bladder (Tachibana et al, 1997), prostate (Green et al, 1997) and head and neck squamous carcinomas (Richards et al, 1997), astrocytoma (Van Meir et al, 1992 and malignant melanoma (Schandendorf et al, 1993;Singh et al, 1994). It has been reported that IL-8 acts as an angiogenic factor in lung carcinoma Strieter et al, 1995;Arenberg et al, 1996); however, the function of IL-8 in the other carcinomas has not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Human recombinant IL-8 can induce proliferation and migration of human umbilical vein endothelial cells (HUVECs) and is potently angiogenic when implanted in the rat cornea . Furthermore, IL-8 is a known angiogenic factor for human lung carcinoma (Strieter et al, 1995), human bladder carcinoma (Tachibana et al, 1997) and human prostate carcinoma (Green et al, 1997). The CXC chemokines IL-8 and interferon-α-inducible protein (IP-10) have recently been shown to regulate angiogenic activity in idiopathic pulmonary fibrosis (Keane et al, 1997).…”
mentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) has been reported to be related to angiogenesis promoted by angiotensin II (7,8), but little is known about the effects of AT1R antagonists on the secretion of the other angiogenic factors by cancer cells. In the present study, we used the bladder cancer cell line KU-19-19, which produces multiple cytokines, including granulocyte colonystimulating factor (G-CSF), granulocyte macrophage colonystimulating factor, interleukin-1 (IL-1), IL-6, IL-8, tumor necrosis factor-h, and h-hCG (13,14). Therefore, we investigated the effect of the AT1R antagonist candesartan on the secretion of cytokines by KU-19-19 cells, mainly of angiogenic factors, such as basic fibroblast growth factor, IL-6, IL-8, G-CSF, granulocyte macrophage colony-stimulating factor, and VEGF.…”
mentioning
confidence: 99%
“…KU-19-19 (Tachibana et al, 1995, 1997a, 1997b has recently been established from the advanced bladder cancer patient and has also recently been established from the advanced renal cell carcinoma patient. These two patients had marked leucocytosis.…”
Section: Cell Culturementioning
confidence: 99%
“…We have previously reported that the bladder cancer cell line KU-19-19 produces multiple cytokines; IL-6, IL-8, granulocytecolony stimulating factor (G-CSF) and granulocyte-macrophage colony stimulating factor (GM-CSF) (Tachibana et al, 1997a). IL-1 is well known as one of the key cytokines that can promote the production of these cytokines (Dinarello, 1996).…”
mentioning
confidence: 99%